The Legality of Mandatory Farewell Donations to Graduating Students Based on Article 12 Letter B Of Permendikbud No. 75/2016 on School Committees - Thomy Faisal; Megawati Barthos (Rechtsnormen: Journal of Law, 2024)
Background: The quality of education services requires continuous improvement, as emphasized by the Minister of Education and Culture, Muhadjir Effendy, through the revitalization of the School Committee's duties under the principle of mutual cooperation. Permendikbud No. 75 of 2016 establishes the School Committee as an independent institution composed of parents, school communities, and concerned community leaders. Despite these provisions, practices such as mandatory farewell donations often resemble illegal levies, contradicting legal culture, decency, and public interest. Objective: This study aims to evaluate the legality of mandatory farewell donations under Article 12 Letter B of Permendikbud No. 75/2016, examining their alignment with the principles of mutual cooperation and accountability. Methodology: The research employs a normative and juridical approach, analyzing data through descriptive analysis to interpret legal and cultural aspects. Findings: Mandatory farewell donations are often framed as agreements between schools, committees, and parents but tend to violate the legal culture's substance. These practices undermine public trust in educational institutions and conflict with legal principles aimed at ensuring fairness and decency in education. Conclusion: Mandatory farewell donations contradict the principles of mutual cooperation and accountability, highlighting the need for improved legal awareness and cultural shifts among education providers to prevent illegal levies.